High‐Harmonic Generation Enhancement with Graphene Heterostructures. Issue 19 (18th July 2022) - Alonso Calafell, Irati; Rozema, Lee A.; Trenti, Alessandro; Bohn, Justus; Dias, Eduardo J. C.; Jenke, Philipp K.; Menghrajani, Kishan S.; Alcaraz Iranzo, David; García de Abajo, F. Javier; Koppens, Frank H. L.; Hendry, Euan; Walther, Philip
Abstract: High‐harmonic generation (HHG) in graphene heterostructures, consisting of metallic nanoribbons separated from a graphene sheet by either a few‐nanometer layer of aluminum oxide or an atomic monolayer of hexagonal boron nitride, is investigated. The nanoribbons amplify the near‐field at the graphene layer relative to the externally applied pumping, thus allowing the observation of third‐ and fifth‐harmonic generation in the carbon monolayer at modest pump powers in the mid‐infrared. The dependence of the nonlinear signals on the ribbon width and spacer thickness, as well as pump power and polarization are studied, and enhancement factors (EF) relative to bare graphene reaching 1600 and 4100 for third‐ and fifth‐harmonic generation, respectively, are demonstrated. The work supports the use of graphene heterostructures to selectively enhance specific nonlinear processes of interest, an essential capability for the design of nanoscale nonlinear devices. Abstract : Graphene‐based heterostructures enhance high‐harmonic generation in graphene in the mid‐infrared spectral range. In these heterostructures, gold nanoribbons confine the optical field in graphene allowing the observation of up to fifth‐harmonic generation from a monolayer of graphene at relatively low pump powers. The dependence of the enhancement on the nanoribbon width, spacer thickness, pump power, and polarization is studied.